Peranan Penyidik Kepolisian Republik Indonesia Dalam Mengungkap Tindak Pidana Penipuan Penempelan Nomor Call Center Palsu Pada ATM di Wilayah Hukum Kepolisian Sektor Tampan Pekanbaru - Ferdian, Wan Gilang; Effendi, Erdianto; ', Erdiansyah (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2017)
Indonesian National Police is the law enforcement institutions, in accordance with the basic tasks set out in the Police Act No. 2 of 2002 on the Indonesian National Police, namely as protector, steward and law enforcement. In this advanced era, make payments through online transactions or credit card is considered safer and easier than having to bother carrying cash because of the risk being robbed. But credit or debit cards are also not free from the threat of crime. Cases which the author adopted in this study is about a fraud case with the mode of attachment of the fake call center number at the ATM machine.Based on case data that was obtained from the Police Sector Tampan on crimes committed on the ATM machine in the District Tampan, that in 2015 there were 6 cases. as well as the number of cases is increasing in the last three years. In this case relates to the role of the police investigator republic of Indonesia in exposing criminal fraud attachment Call Center number at an ATM in the jurisdiction of the Police Sector Tampan Pekanbaru City. The purpose of this thesis, namely First, Role Investigator Police of the Republic of Indonesia in exposing criminal fraud attachment of a number of false call centers at the ATM in Jurisdiction Police Sector Tampan Pekanbaru, two barriers in exposing Crime Fraud Adherence Number Call Center Fraud at ATMs in the jurisdiction Tampan Pekanbaru Police Sector, Third efforts to overcome obstacles in uncovering Crime Fraud Call Center Number Adherence to the ATM in the jurisdiction of Police Sector Tampan Pekanbaru.This type of research can be classified in this type of sociological juridical research, because this research author directly conduct research on the location or point studied to provide complete and clear picture of the issues examined. This research was conducted in the Police Sector Tampan ,Pekanbaru city, while the sample population is a whole party with regard to the issues examined in this study, the data source used the primary data, secondary data, and the data tertiary, data collection techniques in this research with questionnaires, interviews, and review of the literature.From the research there are three main issues that can be inferred. First, in exposing criminal fraud pasting fake call center number at an ATM, the investigator takes the role and concern of the community as well as in terms of security officers thus simplifying the process of inquiry and investigation. Second, the barriers faced by sector police Tampan Pekanbaru in exposing criminal fraud fake call center there are two (2) factors, internal factors and external factors. Third, efforts made by the Police Sector Tampan Pekanbaru in exposing criminal fraud call center number of false attachment has two attempts namely through the preventive and repressive efforts. Suggestions Author, First, The investigator should coordinate with the banks to add security cameras in every corner of the location of the ATM machine that can record all the activities people perform transactions at ATMs or other activities. Secondly, To the ATM card users should always keep the number of complaints given by the bank to be stored in the phone.Keywords: Role – Criminal Act - Fraud